Anthropogenic Causes of Peatland Species Vanishing in the Glinno Ługi Area - Woziwoda, Beata; Komperda, Agata (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2011)
The paper presents information about the occurrence and state of preservation of valuable peat-bog species as well as about the threats facing them. The anthropopressure-related changes which occurred in the habitat of the Glinno Ługi peatland and their influence on the flora are presented and discussed.